Antimicrobial Blue Light Inactivation of Microbial Isolates in Biofilms. Issue 5 (19th September 2019) - Ferrer‐Espada, Raquel; Wang, Ying; Goh, Xueping Sharon; Dai, Tianhong
Abstract : Background and Objectives: Biofilms cause more than 80% of infections in humans, including more than 90% of all chronic wound infections and are extremely resistant to antimicrobials and the immune system. The situation is exacerbated by the fast spreading of antimicrobial resistance, which has become one of the biggest threats to current public health. There is consequently a critical need for the development of alternative therapeutics. Antimicrobial blue light (aBL) is a light‐based approach that exhibits intrinsic antimicrobial effect without the involvement of exogenous photosensitizers. In this study, we investigated the antimicrobial effect of this non‐antibiotic approach against biofilms formed by microbial isolates of multidrug‐resistant bacteria. Study Design/Materials and Methods: Microbial isolates of Acinetobacter baumannii, Candida albicans, Escherichia coli, Enterococcus faecalis, MRSA, Neisseria gonorrhoeae, Pseudomonas aeruginosa, and Proteus mirabilis were studied. Biofilms were grown in microtiter plates for 24 or 48 hours or in the CDC biofilm reactor for 48 hours and exposed to aBL at 405 nm (60 mW/cm 2, 60 or 30 minutes). The anti‐biofilm activity of aBL was measured by viable counts. Results: The biofilms of A. baumannii, N. gonorrhoeae, and P. aeruginosa were the most susceptible to aBL with between 4 and 8 log10 inactivation after 108 J/cm 2 (60 mW/cm 2, 30 minutes) or 216 J/cm 2 (60 mW/cm 2, 60 minutes) aBL were delivered in the microplates. On the contrary, the biofilms of C. albicans, E. coli, E. faecalis, and P. mirabilis were the least susceptible to aBL inactivation (−0.30, −0.24, −0.84, and −0.68 log10 inactivation, respectively). The same aBL treatment in biofilms developed in the CDC biofilm reactor, caused −1.68 log10 inactivation in A. baumannii and −1.74 and −1.65 log10 inactivation in two different strains of P. aeruginosa . Conclusions: aBL exhibits potential against pathogenic microorganisms and could help with the significant need for new antimicrobials in clinical practice to manage multidrug‐resistant infections. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.